Effects of estradiol on fat in men undergoing androgen deprivation therapy: a randomized trial. Issue 1 (30th November 2021) - Russell, Nicholas; Hoermann, Rudolf; Cheung, Ada S; Zajac, Jeffrey D; Handelsman, David J; Grossmann, Mathis
Abstract: Objective: Indirect evidence suggests that the effects of testosterone on fat mass in men are dependent on aromatization to estradiol (E2). However, no controlled study has assessed the effects of E2 in the absence of testosterone. Design: Six-month randomized, placebo-controlled trial with the hypothesis that men randomized to E2 would reduce their fat mass. Methods: Seventy-eight participants receiving androgen deprivation therapy for prostate cancer were randomized to 0.9 mg of 0.1% E2 gel per day, or matched placebo. Dual x-ray absorptiometry body composition was measured at baseline, month 3, and month 6. The primary outcome was total fat mass. Results: Serum E2 increased in the estradiol group over 6 months compared to placebo, and mean-adjusted difference (MAD) was 207 pmol/L (95% CI: 123–292), P   < 0.001. E2 treatment changed total fat mass, MAD 1007 g (95% CI: 124–1891), but not significantly, so P  = 0.09. There were other consistent non-significant trends toward increased proportional fat mass, MAD 0.8% (95% CI: 0.0–1.6), P = 0.15; gynoid fat, MAD 147 g (95% CI: 2–293), P  = 0.08; visceral fat, 53 g (95% CI: 1–105) P  = 0.13; and subcutaneous fat, MAD 65 g (95% CI: 5–125), P  = 0.11. Android fat increased, MAD 164 g (95% CI: 41–286), P  = 0.04. Conclusion: Contrary to our hypothesis, we provide suggestive evidence that E2 acting in the absence of testosterone, may increase total and regional fat mass in men. Given the premature closure of clinical trials due to the COVID pandemic, this potentially important observation should encourage additional studies to confirm or refute whether E2 promotes fat expansion in the absence of testosterone.